2013
DOI: 10.1159/000345983
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 as a Biomarker for Alzheimer’s Disease: A Study with Brazilian Elderly

Abstract: Alzheimer’s disease (AD) is the most common cause of dementia in people above age 65. Platelet studies with ADAM10 have shown that its expression is reduced in AD patients. The aim of this research was to compare the platelet levels of ADAM10 protein in two Brazilian elderly groups, considering the stages of the disease. The SDS-PAGE technique followed by Western blotting was used. Data were analyzed using comparison, correlation and association statistical methods. The results showed reduced platelet ADAM10 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 47 publications
(40 reference statements)
3
32
0
2
Order By: Relevance
“…Both ADAM10 and ADAM17 have been implicated in the development of neurodegenerative diseases such as Alzheimer’s disease [25, 58, 59]. Studies have also shown that ADAM10 expression is widespread in the CNS compared to a more restricted ADAM17 expression [31].…”
Section: Discussionmentioning
confidence: 99%
“…Both ADAM10 and ADAM17 have been implicated in the development of neurodegenerative diseases such as Alzheimer’s disease [25, 58, 59]. Studies have also shown that ADAM10 expression is widespread in the CNS compared to a more restricted ADAM17 expression [31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a reduction of α-secretase protein level in platelets of early stage AD patients [30, 144], in line with attenuated release of sAPP-α from thrombin-activated AD platelets [145]. In addition, an increased activity of β-secretase was indirectly shown by a decreased ratio of its 37/56 kDa fragments from two different groups [143, 144].…”
Section: Reviewmentioning
confidence: 99%
“…In previous studies we have reported a marked reduction in ADAM10 platelet protein levels in CDR (Clinical Dementia Rating) subgroups compared to non-AD patients (Colciaghi et al, 2002;Manzine et al, 2013) and APP, BACE1 and ADAM10 alterations in platelets already in the very early stages of the disease in which dementia can be barely inferred by neuropsychological assessments (Colciaghi et al, 2004). Since ADAM10 is the most important a-secretase involved in APP cleavage, in this work we raise the following question: is ADAM10 protein reduction in the blood of AD patients a consequence of a decrease in ADAM10 transcription?…”
Section: Introductionmentioning
confidence: 94%